What part of my work don't you understand?
u - √2 = 3
u - 1.414 = 3
u = 4.414
u-2√2=3. please show work
4 answers
the answer should be 9
sorry. u-2√u=3
let x = sqrt u
then
x^2 - 2 x = 3
x^2 - 2 x - 3 = -
(x-3)(x+1) = 0
x = 3 or x = -1
try sqrt u = 3 then u = 9
9 - 6 = 3 Yes
try sqrt u = -3 , that is an imaginary number, forget it
so
u = 9
then
x^2 - 2 x = 3
x^2 - 2 x - 3 = -
(x-3)(x+1) = 0
x = 3 or x = -1
try sqrt u = 3 then u = 9
9 - 6 = 3 Yes
try sqrt u = -3 , that is an imaginary number, forget it
so
u = 9